O Espaço Como Obra: Reinterpretação E Preservação Da Arquitetura Eclética No Caso Do Palácio Do Café De Santos-Sp - Faria, Indira Ferreira [UNIFESP] (2017)
The discussion about the preservation of the eclectic architecture and its interior will be represented here by the analysis of the trading room - the main area of the Coffee Palace of Santos-SP (1922) - with its furniture and integrated arts. Considering the relationship between the Bourse building and its artistic elements, this research intends to put in evidence the complementarity amid architecture and arts and the way this relation has been treated in the processes of tipping by the city, state and federal government levels. Are the views of the different processes in relation to eclectic architecture similar or complementary? The way these relationships are built in the project and the way they are treated in the propertyambit are the questions that we intend to answer in this research.